2012
DOI: 10.1177/0954407012453815
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of disc brake squeal propensity through a fully coupled transient thermomechanical model

Abstract: This paper presents a fully coupled transient thermomechanical analysis of a disc brake that takes into account the so-called ‘rotating-heat-source’ effect. Results from this are used to inform the time-based extraction of system eigenvalues that permit quantification of the squeal propensity of the brake. The model performance is validated against a series of dynamometer tests, based upon the SAE J2521 drag brake test schedule, in which the ability of the model to predict the fugitive nature of the squeal pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…[15][16][17] Much research work has been performed during the past few decades to identify and analyze the factors influencing squeal noise and their interaction mechanisms, both through experimental tests 5,18,19 and through numerical approaches. [20][21][22][23][24] In addition, some corresponding reviews have been published [25][26][27][28] and provide a better understanding of the brake squeal phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] Much research work has been performed during the past few decades to identify and analyze the factors influencing squeal noise and their interaction mechanisms, both through experimental tests 5,18,19 and through numerical approaches. [20][21][22][23][24] In addition, some corresponding reviews have been published [25][26][27][28] and provide a better understanding of the brake squeal phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…Young's modulus change, material and shims shear modulus, and some geometrical effects such as the hat torsional stiffness, Ishii-Dodson et al [15]. The commonly called 'rotating-heat-source' effect can be taken into account with the introduction of a fully coupled thermo-mechanical analysis before executing an instability study as demonstrated by Hassan et al [16], [17], [18] and using complex eigenvalue technique by…”
Section: Symbolmentioning
confidence: 99%
“…It can influence tangential in-plane modes of vibrations, Young's modulus change, shear modulus of material and shims, and some geometrical effects such as the hat torsional stiffness. 15 The commonly called 'rotatingheat-source' effect can be taken into account with the introduction of a fully coupled thermo-mechanical analysis before executing an instability study as demonstrated by Hassan et al [16][17][18] and using the complex eigenvalue technique by Kung et al 19 The finite element (FE) method allows an accurate representation of complex geometries and boundary/loading conditions, which traditional lumped parameter techniques cannot address. Magnier et al 20 successfully studied the influence of pad/disc contact on brake squeal.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] In general, friction can dissipate the energy of systems and act as a stabilization mechanism; however, it can also excite vibration in engineering and daily life under certain circumstances. [6][7][8] One important kind of friction-induced vibration is the stick-slip oscillation which consists of two kinds of motion schemes: a stick regime in which the friction pair moves together and a slip regime in which there is relative motion between them. 9,10 Stick-slip oscillation widely exists in many different fields.…”
Section: Introductionmentioning
confidence: 99%